2020
DOI: 10.1002/smtd.202000526
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Nanobelts as an Excellent Bifunctional Oxygen Catalyst: Insight into the Subtle Changes in Structure and Synergistic Effects of Bimetallic Metal‐Organic Framework

Abstract: In the published version of our articles, the details for Figure 3d,e are incorrect; absence of satellite peaks of R2 in Figure 3d. When processing the XPS data, the authors misarranged the order of R1 and R2, resulting in errors. The correct details for Figure 3d,e is changed as follows: Figure 3. XPS spectrum of the: a) survey; b) C 1s; c) O 1s; d) Co 2p, and e) Ni 2p.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The peaks at 466.0 and 487.0 eV correspond to Ru x + 3p 3/2 and Ru x + 3p 1/2 , respectively. Compared with O-RuNi@C-350, because of the electron transfer from Ni to Ru, the 3p 3/2 peaks of Ru 0 and Ru x+ in O-RuNi@C-400 negatively shifted by ∼0.81 and 0.41 eV, respectively. As shown in O 1s spectrum of O-RuNi@C-400 (Figure d), the peaks at ∼533.6, 531.9, and 530.2 eV correspond to C–O–C, CO, and Ni–O–C, respectively. , As shown in O 1s spectrum of Ni@C-400, we can see the Ni–O–C peak, but compared to O-RuNi@C-400, the Ni–O–C peak is relatively weak. It is also found that the Ni–O–C peak positively shifts as the carbonization temperature increases, while its intensity becomes stronger and then weaker.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The peaks at 466.0 and 487.0 eV correspond to Ru x + 3p 3/2 and Ru x + 3p 1/2 , respectively. Compared with O-RuNi@C-350, because of the electron transfer from Ni to Ru, the 3p 3/2 peaks of Ru 0 and Ru x+ in O-RuNi@C-400 negatively shifted by ∼0.81 and 0.41 eV, respectively. As shown in O 1s spectrum of O-RuNi@C-400 (Figure d), the peaks at ∼533.6, 531.9, and 530.2 eV correspond to C–O–C, CO, and Ni–O–C, respectively. , As shown in O 1s spectrum of Ni@C-400, we can see the Ni–O–C peak, but compared to O-RuNi@C-400, the Ni–O–C peak is relatively weak. It is also found that the Ni–O–C peak positively shifts as the carbonization temperature increases, while its intensity becomes stronger and then weaker.…”
Section: Resultsmentioning
confidence: 83%
“…2 eV correspond to C−O−C, C�O, and Ni−O−C, respectively 30,38. As shown in O 1s spectrum of Ni@C-400, we can see the Ni−O−C peak, but compared to O-RuNi@C-400, the Ni−O−C peak is relatively weak.…”
mentioning
confidence: 86%